MTT Assay에 의한 천연불질의 항 HIV - 1 활성 검색 - 이주실; 남정구; 강춘; 이홍래; 이영종; 신영오 (Journal of bacteriology and virology, 1997)
Methanol and/or boiling water extraction of 201 natural products and subsequent MlT assay using MT-4 cell line was carried out to screen the anti-HIV-1 activity. Among 97 methanol extracts, 7 extracts from Chrysanthemi Indicium Flos, Magnoliae Cortex, Machili Cortex, Reynoutriae Rhizoma, Lithospermi Radix, Agastachis Herba, and Chaenomelis Fructus showed anti-HIV-1 activity and their SI value were 2.25 to 5.77. In addition, among 119 boiling water extracts, 10 extracts from Lonicerae Caulis et Foloium, Elsholiae Herba, Leonuri Herba, Portulacae Herba, Schizonepetae Herba, Curcumae Rhizoma, Amomi Cardamomi Fructus, Cirsii Radir et Herba, Carpesii Herba, and Siegesbeckiae Herba showed anti-HIV-1 activity and their SI value were 1.30 to 7.64. Methanol extracts of above seven natural products were fractionated and the anti-HIV-1 activity of each fraction was examined. Extraction was carried out with hexane, chloroform, butanol, and water to trace active anti-HIV-1 componets. As a result, the water fraction of Magnoliae Cortex, Machili Cortex, Reynoutriae Rhizoma, Agastachis Herba, Chaenomelis Fructus and the butanol fraction of Chrysanthemi Indicium Flos, Reynoutriae Rhizoma showed anti-HIV-1 activity and their SI value were 1.40 to 8.02. We could reach a conclusion that studies to trace the anti-HIV-1 active component of each natural products in further fractionation and to identify its structure by Infrared spectroscopy, NMR spectroscopy and gel permeation chromatography were needed.